IMPLEMENTATION OF PSYCHOLOGICAL SERVICES IN PRESCHOOL EDUCATION: SCIENTIFIC AND PRACTICAL APPROACHES - Rajabova Muhayyo Yusupovna (American Journals, 2024)
This article is devoted to the study of scientific and practical approaches to the introduction of psychological services in preschool educational institutions. The article analyzes the importance of psychological services in preschool education, the scientific basis of their introduction, and practical experiences. The positive impact of psychological services on the development of children, the importance of cooperation with parents and educators, as well as methods of effective organization of psychological services are highlighted. The results of the article suggest recommendations aimed at the further development of psychological services in the preschool education system and their quality improvement.
Keywords: Preschool education, psychological service, child development, scientific foundations, practical approaches, psychological support, cooperation with parents, quality of education.